Measuring creative thingking skills of vocational high school students on dynamic electricity: a case study - Roni Permana, Roni Permana (Universitas Mandiri, 2023)
Creative thinking is a precise significant ability of 21st century education. Consequently, students are essential to must this ability to be applied in physics learning especially in the field of vocational. This study purposes to quantity students' creative thinking abilities about Dynamic Electricity. Examples remained busy by purposive sample method. Applicants in this study were 22 K-12 students of vocational students in Subang city. The implements used are three essay questions with four aspects that are turned off. The results showed that the average value was 43.43 with a low category. Consequently, students' creative thinking skills about Dynamic Electricity are still relatively low.